HUBUNGAN PREFERENSI MAKAN, PENGARUH TEMAN SEBAYA, ASUPAN ZAT GIZI MAKRO DAN PAPARAN SOSIAL MEDIA DENGAN KEJADIAN GIZI LEBIH DI SMA NEGERI 6 KOTA DEPOK - Krisanti Nurbaiti (2023)
Overnutrition is defined as an increase in body weight due to the accumulation of excess body fat. Overnutrition among adolescents has become an increasing nutritional issue in recent years. If left unaddressed, overnutrition can lead to health complications such as hypertension, fatty liver, diabetes, heart disease, and cancer. The aim of this study was to determine the relationship between eating preferences, peer influence, macro-nutrient intake, and social media exposure with the incidence of overnutrition among adolescents in SMA Negeri 6 Depok. This study employed a cross-sectional study design using stratified random sampling technique with a sample size of 108 individuals. Data analysis was conducted using Chi-Square and Fisher's exact tests. The bivariate data analysis revealed a significant association between eating preferences (p=0.019; OR=8.4), peer influence (p=0.006; OR=4.3), energy intake (p=0.03; OR=3.3), protein intake (p=0.036; OR=3.3), and carbohydrate intake (p=0.047; OR=4) with the incidence of overnutrition. However, there was no significant association found between fat intake (p=0.085) and social media exposure (p=0.405) with the incidence of overnutrition among adolescents in SMAN 6 Depok. Adolescents are advised to pay more attention to their healthy food intake, develop healthy eating preferences, and utilize peer influence to adopt good eating behaviors in order to prevent overnutrition.